The Development and Organization of Newborn Screening Programs in Turkey. Issue 1 (27th December 2013) - Tezel, Başak; Dilli, Dilek; Bolat, Hilal; Şahman, Hatice; Özbaş, Sema; Acıcan, Deniz; Ertek, Mustafa; Köse, Mehmet Rıfat; Dilmen, Uğur; ,
<x xml:space="preserve">Abstract</x> Background Newborn screening tests have been designed to identify infants with severe disorders that are relatively prevalent and treatable or controllable. Comparing to other countries, the incidence of these diseases are very high in Turkey where the rate of consanguineous marriage is high. Methods In this article, it is aimed to evaluate the development and organization of newborn screening programs in Turkey which include phenylketonuria, congenital hypothyroidism and biotinidase deficiency screenings. The point reached today, limitations of the program, expectations and projects for the future are discussed. Results Today, the point reached in screening programs of the country is appreciable. While the screening rate of the live born babies was 4, 7% in 1987, this rate reached to 95% by 2008. Predicted target for newborn screening program at the strategic plan of Ministry of Health for 2010–2014 was to enhance this rate above 95% by the end of 2012. It seems that the envisaged goal has been reached. Conclusion National newborn screening program appears to be conducted successfully and extensively as a result of political determination and performance of health care workers who are in charge of this program. Nevertheless, limited numbers of the nutrition and metabolism clinics and specialists on these branches have caused some access difficulties, waste of time, and financial loss. Therefore, special planning to improve quality and the number of the clinics would be useful.